Supervisor Bottom-Line Mentality, Performance Pressure, and Workplace Cheating: Moderating Role of Negative Reciprocity - Kamran, Komal; Azam, Akbar; Atif, Mian Muhammad (Frontiers in Psychology, 2022)
Employee cheating at the workplace has reached epidemic proportions and is putting a significant dent on the revenues of corporations. This study evaluates workplace cheating behavior as a consequence of supervisor bottom-line mentality with performance pressure as the mediating mechanism. Most importantly, it scrutinizes the moderating function of negative reciprocity belief in the relation between bottom-line mentality, performance pressure and cheating in a moderated17 mediation model, through the lens of displaced aggression theory. We systematically conduct time18 lagged studies in two different populations (Pakistan and United States). Data analysis reveals that (1) bottom-line mentality positively influences workplace cheating behavior through performance pressure and (2) negative reciprocity moderated this indirect relationship. Theoretical and practical implications are discussed.